Marketing Syariah: Studi Analisis Produk Kenzie di Gudo Jombang (IAIN Tulungagung, 2018)
Abstract: This research is based on the rise of businessmen who are just looking for profit, and also the phenomenon that occurs based on the reality of the current trend, many businesses that use sharia or religion as a booster of material gain, or politicization. But it is different with the business that is doing by manufacturers from Jombang, creating something simple to be extraordinary, bringing benefits and even blessings. Positive small things and done according to the demands of sharia bring benefits and blessings. There are some purpose of this study,the first is to understand sharia marketing, secondly, to analyze the implementation of sharia marketing on the business of The otak- otak of Kenzi's. This research was conducted to business owners of the otak- otak kenzie in Blimbing Village, Gudo Jombang, employees and customers or the community. The process of collecting data by interview method, observation and documentation. Using qualitative descriptive analysis is to describe the results of interviews of respondents, then analyze it with the theory. The results of this research is to show that the business owner of the kenzie product implicitly understands and implements the syariah values ​​in its business activities. Sharia implementation is reflected on shariah marketing strategy, which is the segmentation of the public market and target market of upper middle economic society and to atrack the hearts of its consumers with friendly and honest service. In the case of shariah marketing tactic, including are halal products, standard price according to sharia, which is related to the location of businesssworth according to syaraiah. In sharia marketing value, there are some value,that can given some benefits for consumers including: healthy, halal elements and well in accordance with the Qur'an that ordered humans to eat clean food, take a holy and healthy way. From the shariah spiritual image related to the principle of honesty of hospitality that must be owned by a businessman,he feels that Allahis always watching everywhere, so both the value of sharia and the principles of sharia is very important and useful in the business world. And from the existing phenomenon Sharia-labeled marketing is not Islamization or religious commercialism, but it is a way asameans in offering products produced in a business, the impact of the economy of a society will also increase, religion is not used as demolisher of the economy, to seek material , but sharia or religionas measureand also as a rule that underlies human behavior. Religion and economics can not be compared, but go hand. Religion is notto be traded in economic interests, but the advanced of the economy is due to the religious rules. Key word: marketing, sharia marketing, analyze of business product